1986
DOI: 10.1111/j.1365-2125.1986.tb05228.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of atenolol and enalapril on memory during treatment for essential hypertension.

Abstract: A randomized single‐blind study was designed to compare the performance on memory tests requiring recall of information relevant to everyday life of two groups of hypertensive patients. One group of 13 patients were taking a beta‐adrenoceptor blocker (atenolol) and the other group of 12 patients received the angiotensin‐converting enzyme inhibitor (enalapril). The results suggested that when compared with placebo the group of patients treated with enalapril showed no changes in memory function, whilst there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…Costall et al, 1989), it is of particular interest that neither the present study nor those of Lichter et al (1986) or Deary et al (1991) showed any specific benefit of this class of drug in hypertensive patients. However, effects on memory in normal human subjects have not been found consistently (e.g.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…Costall et al, 1989), it is of particular interest that neither the present study nor those of Lichter et al (1986) or Deary et al (1991) showed any specific benefit of this class of drug in hypertensive patients. However, effects on memory in normal human subjects have not been found consistently (e.g.…”
contrasting
confidence: 65%
“…Secondly, comparison of the percentage of correct responses in the two studies again suggests that both batteries of tests are sensitive: subjects tend to score in the middle range, with no floor or ceiling effects obscuring potential changes. Furthermore, in each case the tests are sensitive enough to reveal some differences, either between drug conditions (Lichter et al, 1986) or between test occasions (the present study). With respect to the present tests, comparison of data from the younger subjects in the pilot study with the data from the hypertensive patients revealed significantly higher scores for the younger subjects, for all indices except those relating to the 'Objects' sub-test.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In order to compare our results with those made with the same tests by Lichter et al (1986), the shopping list and the phone numbers were tested immediately after each trial. The 252S B. Dietrich & W. M. Herrmann first test of immediate recall was performed after the fourth trial, with the following subtest separating trial 4 from the first test so that the learned material could be consolidated (Figure 2).…”
Section: Memory Testsmentioning
confidence: 99%